Correlating instructional leadership practices of school administrators with teachers competencies - Villa, Frederick T.; Tulod, Razel C. (Linguistics and Culture Review, 2021)
The study correlated the instructional leadership practices of school administrators with teachers’ competencies. Using a sample size of 208 teachers and 22 school administrators chosen as respondents with a descriptive-correlational research design, the study has able to find out that the demographic profile of the respondents were females, with MA units, in the position of teacher II, and were widowed. On the average, the number of years in service, current school and position of the teachers was 5 years and above. It further revealed that the respondents’ evaluation of the instructional leadership practices of School administrators showed an agreed response. It showed that on planning to modify and improve instruction on curriculum improvement was the highest to follow changes like the k to 12 and be able to globally compete to the outside countries. It also showed that the performance teachers perceived impact through instructional leadership practices of their administrators which showed an agreed response. The teacher’s competence on learning environment was the highest to be able to know the dedication of the teachers to teach and make students learned from them. It showed that there is no significant relationship between instructional leadership practices of School Administrators and Teachers’ Performance.